Deradikalisasi dalam Keluarga untuk Menangkal Ekstrimisme dan Radikalisme pada Mahasiswa - Asmuni, Hadiqoh (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2022)
Extremism and radicalism are becoming one of our country's most pressing issues.When one radical group's goals are not achieved, violence symptoms become commonplace.The primary target audience for radical groups that spread extremism is children. As a result, the government is taking preventative measures, including through educational establishments, teachers, and curriculum, to raise a younger generation with a more nationalistic outlook as well as a more tolerant and moderate attitude. In an effort to combat extremism and radicalism, deradicalization can be accomplished through the provision of adequate explanations regarding Islam, the promotion of dialogue in Islamic religious education, the monitoring of activities and materials related to religious assistance, and the introduction and implementation of multicultural education.A solution to the problem of radicalism that targets today's younger generation is to strengthen the Islamic education curriculum in educational institutions based on Islamic moderation